APPLICATION OF PIEZOELECTRIC AND SEISMOELECTROKINETIC PHENOMENA IN EXPLORATION GEOPHYSICS: REVIEW OF RUSSIAN AND ISRAELI EXPERIENCES - Neishtadt N.M.; Eppelbaum L.V.; Levitski A.G. (My University, 2006)
Systematic research of piezoelectric and seismoelectrokinetic phenomena in the context of exploration geophysics began in the former Soviet Union in the mid-1950s. These phenomena are manifested by electrical and electromagnetic (EM) processes that occur in rocks under the influence of elastic oscillations triggered by shots or mechanical impacts (hits). This paper presents a classification of piezoelectric and seismoelectrokinetic phenomena, which is based on the analysis of abundant theoretical, laboratory, and field data accumulated mainly by Soviet, Russian, and Israeli researchers. This classification divides the above phenomena into the following types: (1) the seismoelectrokinetic (electrokinetic) phenomenon E, which occurs in poly-phase media because of the mutual displacement of the solid and liquid phases; (2) the piezoelectric phenomenon, which occurs in rocks that contain piezoactive minerals; (3) the shot-triggered phenomenon, observed in rocks in the vicinity of a shotpoint or hit point; (4) the seismoelectric phenomenon I, manifested by the change of the electric current passing through rock; and (5) high-frequency impulse EM radiation, generated by massive base-metal bodies. This paper describes these five phenomena in detail - their nature, manifestation patterns, and registration techniques. Because the manifestation patterns of the phenomena differ in various types of rock, the phenomena can be used as a basis for geophysical exploration techniques. The piezoelectric method is an example of a successful application of piezoelectric and seismoelectrokinetic phenomena in exploration geophysics. This method was developed in the former Soviet Union, and it has been applied successfully in mineral exploration and research in Russia and, recently, in the West. The method uses a new geophysical parameter: piezoelectric activity of rocks, ores, and minerals. It enables direct exploration for pegmatite, apatite-nepheline, sphalerite, and ore-quartz deposits of gold, tin, tungsten, molybdenum, zinc, crystal, and other raw materials. This method also differentiates rocks such as bauxites and kimberlites from host rocks by their electrokinetic properties. © 2006 Society of Exploration Geophysicists. All rights reserved.
Keywords: GEOMAGNETISM; GEOPHYSICAL PROSPECTING; GOLD; MINERALS; MOLYBDENUM; PIEZO ELECTRICITY; ROCKS; TERRESTRIAL ELECTRICITY; TIN; TUNGSTEN; ZINC